Pengembangan Pendidikan Inklusif Program Studi Magister Manajemen Pendidikan Islam UIN Sunan Kalijaga - Rafi Pradipa; Karwadi Karwadi; Nur Saidah (Gemi: Jurnal Penelitian dan Pengabdian, 2026)
Inclusive education in higher education institutions still faces various challenges, including social stigma, inadequate infrastructure, lack of lecturer competence, unsupportive policies, digital access gaps, and limited psychosocial services. This study aims to analyze the design and implementation of inclusive education development in the Master Program of Islamic Education Management (MPI), Sunan Kalijaga State Islamic University (UIN Sunan Kalijaga) Yogyakarta. The research employed a descriptive qualitative approach with data analysis based on observation, interviews, and document study. The findings reveal that the MPI Study Program has developed an integrated inclusive education ecosystem through: (1) formal policies coordinated with the Disability Service Center (PLD), (2) flexible Outcome-Based Education (OBE) curriculum, (3) adaptive academic and non-academic services, (4) lecturer mentoring and peer buddy system, and (5) internalization of core values including rahmatan lil ‘alamin, equal access, humanistic communication, adaptive mentoring, and sustainable development. Nevertheless, challenges remain, such as uneven policy socialization, limited facilities, and inter-unit coordination gaps. The study concludes that inclusive education in the MPI Study Program has transformed from a normative concept into sustainable operational practice, with the potential to serve as a model for other study programs in Islamic higher education institutions. Strengthening socialization, improving infrastructure, and conducting regular evaluations are key to ensuring the continuity of inclusivity.